2022
DOI: 10.1017/s1463423621000840
|View full text |Cite
|
Sign up to set email alerts
|

Building and changing business models: a qualitative study among Dutch physiotherapy primary healthcare organisations

Abstract: Aim: To gain insights into what business model-building and model-changing aspects make physiotherapy primary healthcare organisations (PTPHOs) attain and sustain superior performance in a changing environment, according to their managers. Background: Since 2006, the transition towards managed competition in the Dutch healthcare market has been intended to improve the performance of primary healthcare organisations like PTPHOs. In such a market, competition on efficiency with reimburseme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…This makes the use of a business model potentially an important pillar for the management of AMCs. This was recently confirmed by IJntema et al [21]. Their study shows that organisations achieve better performance in a changing environment by using a business model.…”
Section: Plos Onementioning
confidence: 53%
See 1 more Smart Citation
“…This makes the use of a business model potentially an important pillar for the management of AMCs. This was recently confirmed by IJntema et al [21]. Their study shows that organisations achieve better performance in a changing environment by using a business model.…”
Section: Plos Onementioning
confidence: 53%
“…In the IJntema study mentioned above, Dutch managers experience and emphasise the importance of using the same business model in the care chain to achieve and maintain better performance. At the same time, however, they note that this still varies widely in practice [21]. Finally, a European comparison of AMC governance has shown that AMCs struggle to adapt to changing circumstances [2].…”
Section: Barriers and Challengesmentioning
confidence: 99%